Preparation method and application of anti-static filter paper

By dispersing carbon fibers in the fiber filter material and surface treatment with zein solution, anti-static filter paper is prepared, which solves the electrostatic problem of fiber filter material during use, and improves the anti-static property, strength and water resistance of the paper.

CN119956625APending Publication Date: 2025-05-09ZHEJIANG HONGLUN PAPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510335872.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

Existing fiber filter materials are prone to static electricity during use, resulting in device damage or fire. The conductive modification of fibers will reduce the fiber strength and require a large amount of chemical reagents. The conductive substances are prone to fall off during long-term use, resulting in unstable performance.

Method used

The carbon fiber is dispersed in alkali urea cellulose solution, and the carbon fiber dispersion is prepared, and the paper is formed by suction filtration and hot pressing, and then soaked and dried in the zein solution, and heat sealing treatment is carried out to prepare an anti-static filter paper.

Benefits of technology

The antistatic property, strength and water resistance of fiber filter paper are improved, avoiding the problems of electrostatic damage and unstable performance. At the same time, through the uniform distribution of carbon fiber and the film-forming characteristics of zein, the filtration capacity and use stability of the paper are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119956625A_ABST
    Figure CN119956625A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of anti-static filter paper, and relates to the technical field of anti-static filter paper. The method comprises the following steps: firstly preparing a carbon fiber dispersion liquid with uniform composition, then diluting the carbon fiber dispersion liquid with water / ethanol to precipitate cellulose fibers again, forming paper in a suction filtration manner, and modifying the paper with zein to finally prepare the anti-static filter paper with good air permeability, high strength and good water resistance. And the anti-static filter paper prepared by the method provided by the invention can be used for manufacturing a filter material. According to the technical scheme, the carbon fibers are added in the preparation process of the paper, so that the paper is endowed with antistatic property, the strength of the paper can be improved, and the paper is endowed with excellent use performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic filter paper, and in particular to a preparation method and application of antistatic filter paper. Background Art

[0002] Due to its high specific surface area and loose porous three-dimensional structure, fiber filter materials have high filtration efficiency and low flow resistance for particulate matter in gas and liquid, and they dominate the filter materials. Among them, plant fiber filter materials also have the advantages of low cost, biodegradability, renewability, and green environmental protection. In addition to the strength indicators such as tensile strength, tear strength, and burst resistance required by general industrial paper, filter materials must also have high air permeability and filtration efficiency. In addition, during use, the gas / liquid medium containing a large number of particles will produce static electricity when passing through the filter paper at high speed, causing damage to the equipment and even causing fire problems. To improve this problem, a common method is to modify the fiber to be conductive during the preparation of the fiber filter material, such as improving the conductivity of the fiber by adsorbing or modifying the fiber with a conductive polymer. However, the conductive modification of the fiber will reduce the fiber strength and require the use of a large amount of chemical reagents. The adsorbed conductive substance will inevitably cause the conductive substance to fall off during long-term use, resulting in unstable performance of the filter material.

[0003] In view of this, it is necessary to design a preparation method of antistatic filter paper and its application to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of antistatic filter paper and application thereof.

[0005] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing an antistatic filter paper, comprising the following steps:

[0006] S1. After mixing sodium hydroxide, urea and water, adding cellulose, and fully dispersing them to obtain an alkali urea cellulose solution; dispersing carbon fibers in the alkali urea cellulose solution to obtain a carbon fiber dispersion;

[0007] S2, diluting the carbon fiber dispersion obtained in step S1, filtering the obtained solution to obtain a dry paper web, and subjecting the solution to a hot press drying treatment;

[0008] S3, soaking the dry paper obtained in S2 in the zein solution for 1-5 minutes, taking it out, drying it and heat-sealing it, so as to obtain the antistatic filter paper.

[0009] Preferably, in step S3, the zein solution is obtained by dissolving zein in an ethanol solution, and the concentration thereof is 1-20 wt %; the mass percentage of the ethanol solution is 60-90%.

[0010] Preferably, in step S1, the length of the carbon fiber is 2-8 mm, and the mass percentage of the carbon fiber in the carbon fiber dispersion is 0.025-0.125%.

[0011] Preferably, the dilution process is carried out as follows: water or ethanol is added to the carbon fiber dispersion, and the dilution multiple is 1-5 times.

[0012] Preferably, in step S1, the mass ratio of sodium hydroxide, urea and water is 7:12:81, and the mass percentage of cellulose in the alkali urea cellulose solution is 0.1-0.5wt%.

[0013] Preferably, in step S2, the filtration is performed as follows: vacuum filtration is performed using a 60-100 mesh corrosion-resistant mesh.

[0014] Preferably, in step S2, the temperature of the hot pressing drying treatment is 80-120°C and the time is 5-15 minutes.

[0015] Preferably, in step S3, the temperature of the heat sealing treatment is 110-180°C and the pressure is 0.1-0.5 MPa.

[0016] In particular, the antistatic filter paper prepared by the preparation method of the present invention can be used to manufacture filter materials.

[0017] The beneficial effects of the present invention are:

[0018] 1. The preparation method of the antistatic filter paper provided by the present invention is to prepare a carbon fiber dispersion with uniform composition, dilute it with water / ethanol to make the cellulose fiber therein reprecipitate, form paper by suction filtration, and modify the paper with zein, and finally obtain air filter paper with good air permeability, high strength, good water resistance and antistatic. In the above technical scheme, by adding carbon fiber in the preparation process of paper, antistatic property can be provided for paper, because carbon fiber and cellulose fiber are stably present in the solution phase before paper forming, and the two are in a uniformly mixed state, so the two fibers in the paper are still in a uniformly mixed state after paper forming, and after fiber regeneration and forming process, the fiber and carbon fiber are evenly distributed in the paper structure, the internal composition of the paper is uniform, and the pore structure size is uniform, which is conducive to improving the filtering capacity of the paper, avoiding the pores of the paper being blocked during use, and affecting the filtering property of the paper; secondly, adding carbon fiber can give the paper antistatic property and conductivity, and give the paper excellent use performance.

[0019] 2. The preparation method of the antistatic filter paper provided by the present invention improves the antistatic property of the paper by adding carbon fiber. Since the carbon fiber, as the fiber forming the paper, exists stably in the paper, it will not separate from the paper even after long-term use, and the stability of the paper is excellent.

[0020] 3. The preparation method of the antistatic filter paper provided by the present invention can achieve precise control of paper performance by selecting conditions such as the amount of carbon fiber added and the dilution multiple of the carbon fiber dispersion before papermaking. The process is easy to operate and can achieve large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the structure of the antistatic filter paper proposed by the present invention;

[0022] Figure 2 This is a microscope image of the antistatic filter paper prepared in Example 1 of the present invention at a magnification of 100;

[0023] Figure 3 This is a microscope image of the antistatic filter paper prepared in Example 1 of the present invention at a magnification of 500;

[0024] Figure 4 Conductive effect diagram of the antistatic filter paper prepared in Example 1

[0025] Figure 5 This is an optical photograph of the antistatic filter paper prepared in Example 1 of the present invention;

[0026] Figure 6 This is a microscope image of the filter paper prepared in Comparative Example 1 of the present invention at a magnification of 100;

[0027] Figure 7 This is a microscope image of the filter paper prepared in Comparative Example 1 of the present invention at a magnification of 500;

[0028] Figure 8 It is a comparison chart of dry and wet tensile strength between Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0032] The method for preparing the antistatic filter paper provided by the present invention comprises the following steps:

[0033] S1. Preparation of carbon fiber dispersion: mixing sodium hydroxide, urea and water, adding cellulose, and fully dispersing to obtain an alkali urea cellulose solution; dispersing carbon fiber in the alkali urea cellulose solution to obtain a carbon fiber dispersion;

[0034] S2, preparation of antistatic filter paper: diluting the carbon fiber dispersion obtained in step S1, filtering it to form, and performing hot pressing and drying to obtain a dry paper web;

[0035] S3, soaking the dry paper web in the zein solution for 1-5 minutes, taking it out, drying it and heat-sealing it, so as to obtain the antistatic filter paper.

[0036] In the above technical scheme, filter paper is prepared by using cellulose and carbon fiber as raw materials, and a conductive network structure can be formed in the paper using carbon fiber, thereby improving the antistatic performance of the filter paper; after the paper is formed, the surface of the paper is treated with a zein solution, and its excellent film-forming properties can be used to form a film layer on the surface of the paper. The appearance of the film structure is beneficial to enhancing the interaction between cellulose fibers and cellulose fibers, cellulose fibers and carbon fibers, and carbon fibers and carbon fibers in the paper, and is beneficial to enhancing the bonding stability between the fibers inside the paper, thereby improving the strength of the paper as a whole, and at the same time improving the stability of the conductive network structure; secondly, zein is hydrophobic, and after treating the paper with it, the water resistance of the paper can be improved.

[0037] As an embodiment of the present invention, in step S1, the mass ratio of sodium hydroxide, urea and water is 7:12:81, and the mass percentage of cellulose in the alkali urea cellulose solution is 0.1-0.5wt%.

[0038] As an embodiment of the present invention, in step S1, the length of the carbon fiber is 2-8 mm, and the mass percentage of the carbon fiber in the carbon fiber dispersion is 0.025-0.125%.

[0039] As an embodiment of the present invention, in step S2, the filtration is performed in the following manner: vacuum filtration is performed using a 60-100 mesh corrosion-resistant mesh.

[0040] As an embodiment of the present invention, in step S2, the dilution process is performed as follows: water or ethanol is added to the carbon fiber dispersion, and the dilution multiple is 1-5 times.

[0041] As an embodiment of the present invention, in step S2, the temperature of the hot pressing drying treatment is 80-120°C and the time is 5-15 minutes.

[0042] As an embodiment of the present invention, in step S3, the zein solution is obtained by dissolving zein in an ethanol solution, the mass percentage of the ethanol solution is 60-90%, and the concentration of the zein solution is 1-20wt%.

[0043] As an embodiment of the present invention, in step S2, the drying temperature of the dry paper web after soaking in the zein solution is 60-120° C. and the drying time is 10-60 min.

[0044] As an embodiment of the present invention, in step S2, the temperature of the heat sealing treatment is 110-180°C and the pressure is 0.1-0.5 MPa.

[0045] The preparation method and application of the antistatic filter paper proposed by the present invention are further described below in conjunction with specific embodiments:

[0046] Example 1

[0047] This embodiment prepares an antistatic filter paper, comprising the following steps:

[0048] S1. Sodium hydroxide, urea and water are mixed in a mass ratio of 7:12:8, stirred and cooled to -12°C. When the solution becomes clear and transparent, an appropriate amount of cellulose is added and stirred at -12°C for 30 minutes to obtain a cellulose suspension, wherein the mass percentage of cellulose in the cellulose suspension is 0.1%; an appropriate amount of carbon fiber is dispersed in the alkali urea cellulose solution, ultrasonically dispersed for 10 minutes, and stirred at room temperature for 30 minutes to obtain a carbon fiber dispersion, wherein the mass percentage of carbon fiber in the carbon fiber dispersion is 0.025%;

[0049] S2, adding an equal volume of water to the carbon fiber dispersion prepared in step S1 (i.e., the volume ratio of the carbon fiber dispersion to the water is 1:1), stirring thoroughly and evenly, filtering with an 80-mesh filter to obtain a wet paper web; hot-pressing and drying the wet paper web at 150° C. and 0.3 MPa for 15 minutes to obtain a dry paper web;

[0050] S3, immerse the dry paper web in the zein solution for 2 minutes, take it out, dry it at 60°C for 1.0h, and then heat seal it at 160°C and 0.4MPa to obtain the antistatic filter paper. Figure 1 shown.

[0051] The zein solution is prepared as follows: 10.0 g of zein is added to 100 mL of 85% ethanol solution, and stirred until the zein is dissolved, thereby obtaining the zein solution. It should be noted that the reagents and raw materials used in the embodiments of the present invention can be obtained by purchasing from the market unless otherwise specified.

[0052] Microscope images of the antistatic filter paper prepared in this embodiment at different magnifications are as follows: Figure 2-3 As shown in the figure, the gray-white part is cellulose fiber, and the thinner black fiber is carbon fiber. It can be seen from the figure that cellulose fiber and carbon fiber are mixed together in an orderly manner, and the carbon fibers are interconnected to form a network structure. The appearance of this structure can form a conductive path in the paper, so that the filter paper has good conductive properties, such as Figure 4 As shown, when the paper prepared in this embodiment is used in a reflux circuit containing a battery and a small light bulb, the small light bulb can be illuminated. This result shows that the paper has a certain conductivity, which indirectly shows that the paper has antistatic properties. The optical photo of the antistatic filter paper is shown in Figure 5 As shown in the figure, it can be seen that the paper has a yellow luster and the appearance of the paper is uniform everywhere.

[0053] In order to explore the application potential of the antistatic filter paper prepared in Example 1 in the field of filtration, it was used to filter particles with a particle size of 0.3 μm. According to the "GBT40353-2021 Air Filter Paper" standard test, the filtration efficiency was higher than 85%, which can reach sub-high efficiency air filter paper. The results show that the antistatic filter paper proposed in the present invention can be used in the field of filtration.

[0054] Examples 2 to 5

[0055] The difference between Examples 2 to 5 and Example 1 is that in step S2, the volume ratio of the cellulose dissolving solution to water during the dilution process is different from that in Example 1, and step S3 is not performed. The other experimental conditions and experimental parameters are the same as those in Example 1 and are not repeated here. The volume ratio of the carbon fiber dispersion to water in Examples 1 to 5 and the performance of the air filter paper prepared under the corresponding conditions are shown in Table 1. From the data in the table, it can be seen that with the continuous increase of the dilution ratio, the paper quantity increases first and then tends to stabilize. When the dilution volume ratio is 4:1, the paper quantity and air permeability tend to be stable, and the quantity is 66g / m 2 , air permeability is 217L / m 2 / s.

[0056] Table 1 Volume ratio of carbon fiber dispersion to water in Examples 1 to 5 and properties of filter paper obtained under corresponding conditions

[0057] project Volume ratio <![CDATA[Quantitative (g / m 2 )]]> <![CDATA[Air permeability (L / m 2 / s)]]> Example 1 4:1 66 217 Example 2 1:1 93 72 Example 3 2:1 82 89 Example 4 3:1 71 180 Example 5 5:1 68 216

[0058] Examples 6 to 8

[0059] The difference between Examples 6 to 8 and Example 1 is only that: in step S1, the mass percentage of carbon fiber in the carbon fiber dispersion is different from that in Example 1, and step S3 is not performed. The other experimental conditions and experimental parameters are the same as those in Example 1, and are not repeated here. The mass percentage settings of carbon fiber in Example 1 and Examples 6 to 8 and the properties of filter paper obtained under the corresponding conditions are shown in Table 2. From the data in the table, it can be seen that with the increase of carbon fiber content, the air permeability shows a significant increasing trend, and the resistivity and dry and wet strength are significantly reduced. This is because the carbon fiber is evenly dispersed and forms a conductive network structure in the paper. As its content increases, the conductive performance is significantly improved; at the same time, the increase in carbon fiber reduces the bonding between fibers and increases the void structure, thereby increasing the air permeability, but the reduction in bonding between fibers leads to a significant decrease in dry and wet strength.

[0060] Table 2 The mass percentage of carbon fiber in Example 1 and Examples 6 to 8 and the properties of filter paper obtained under the corresponding conditions

[0061]

[0062] Examples 9 to 12

[0063] The difference between Examples 9 to 12 and Example 1 is only that: in step S3, the concentration of the zein solution used is different from that in Example 1, and the other experimental conditions and experimental parameters are the same as those in Example 1, which will not be repeated here. The concentrations of the zein solutions in Examples 1 and 9 to 12 and the properties of the filter paper prepared under the corresponding conditions are shown in Table 3. From the data in the table, it can be seen that as the concentration of the zein solution continues to increase, the air permeability of the filter paper gradually decreases, and the dry and wet strengths are significantly increased. This is because after the filter paper is soaked in the zein solution, the zein is adsorbed on the surface of the fiber and the carbon fiber, and then after drying and film formation, the zein is bonded between the fiber and the fiber, the fiber and the carbon fiber, and the carbon fiber and the carbon fiber, thereby improving the structural stability of the filter paper and giving the filter paper good water resistance.

[0064] Table 3 Concentrations of zein solutions in Examples 1 and 9 to 12 and properties of filter papers obtained under corresponding conditions

[0065]

[0066] Comparative Example 1

[0067] The only difference between Comparative Example 1 and Example 1 is that step S3 is not performed, that is, the dry paper web is not soaked with the zein solution. Other experimental conditions and parameters are the same as those in Example 1 and will not be described again.

[0068] The microscope image of the filter paper prepared in Comparative Example 1 is as follows: Figure 6 and 7 As shown, Figure 2-3 By comparison, it can be seen that the filter paper is off-white, which is because it has not been soaked and dried by zein, and there are only fibers and carbon fibers in the filter paper. The strength comparison of the antistatic filter paper prepared in Example 1 (after soaking) and Comparative Example 1 (before soaking) is shown in the figure below. Figure 8 As shown, the dry and wet strengths of the air filter paper prepared in Comparative Example 1 are 0.72 kN / m and 68 N / m, respectively, and the resistivity is 8.39 Ω·cm; the dry and wet strengths of the air filter paper prepared in Example 1 are 2.1 kN / m and 82 kN / m, respectively, and the resistivity is 7.93 Ω·cm. The results show that after treatment with zein, the strength and water resistance of the paper can be effectively improved, and the resistivity can be reduced.

[0069] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an antistatic filter paper, characterized in that: The steps include: S1. After mixing sodium hydroxide, urea and water, adding cellulose, and fully dispersing them to obtain an alkali urea cellulose solution; dispersing carbon fibers in the alkali urea cellulose solution to obtain a carbon fiber dispersion; S2, diluting the carbon fiber dispersion obtained in step S1, filtering the obtained solution to obtain a dry paper web, and subjecting the solution to a hot press drying treatment; S3, soaking the dry paper obtained in S2 in the zein solution for 1-5 minutes, taking it out, drying it and heat-sealing it, so as to obtain the antistatic filter paper.

2. The preparation method according to claim 1, characterized in that: In step S3, the zein solution is obtained by dissolving zein in an ethanol solution, and the concentration thereof is 1-20 wt %; the mass percentage of the ethanol solution is 60-90%.

3. The preparation method according to claim 1, characterized in that: In step S1, the length of the carbon fiber is 2-8 mm, and the mass percentage of the carbon fiber in the carbon fiber dispersion is 0.025-0.125%.

4. The preparation method according to claim 1, characterized in that: The dilution process is carried out as follows: water or ethanol is added to the carbon fiber dispersion, and the dilution multiple is 1-5 times.

5. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of sodium hydroxide, urea and water is 7:12:81, and the mass percentage of cellulose in the alkali urea cellulose solution is 0.1-0.5wt%.

6. The preparation method according to claim 1, characterized in that: In step S2, the filtration is performed as follows: vacuum filtration is performed using a 60-100 mesh corrosion-resistant mesh.

7. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the hot pressing drying treatment is 80-120°C and the time is 5-15 minutes.

8. The preparation method according to claim 1, characterized in that: In step S3, the heat sealing treatment is performed at a temperature of 110-180°C and a pressure of 0.1-0.5 MPa. 9.An antistatic filter paper, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the antistatic filter paper according to claim 9 in the field of manufacturing filter materials.